2010
DOI: 10.1111/j.1365-2516.2010.02249.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards comprehensive care in transition for young people with haemophilia

Abstract: In the last two decades, the transition from paediatric to adult care has received increasing attention. Health care professionals have become more aware of the unique needs of adolescents and young adults with chronic illnesses and efforts have been made to support youth through this challenging time of change. For patients with haemophilia and their families, there is little evidence regarding best practice for transition of care. We reviewed the transition literature and current guidelines for transition fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 49 publications
3
93
1
1
Order By: Relevance
“…In these two centres, the policy regarding the start of early prophylaxis and the use of educational material for teaching patients are 12.0 (9-17) 11.0 (8-17) 5.0 (3-9)* 8 (4-14) Time (weeks) 7.5 (5-11) 9.0 (4-15) 12.0 (1-28) 7 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Values are medians (IQR). *Significant differences with the other categories in the row (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In these two centres, the policy regarding the start of early prophylaxis and the use of educational material for teaching patients are 12.0 (9-17) 11.0 (8-17) 5.0 (3-9)* 8 (4-14) Time (weeks) 7.5 (5-11) 9.0 (4-15) 12.0 (1-28) 7 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Values are medians (IQR). *Significant differences with the other categories in the row (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The complex biological, social and emotional changes inherent in adolescence make this increasingly challenging for many teens [2]. A recent study showed that at a median age of 17.2 years, almost 25% of AWH still required parental assistance in hemophilia-related care [3].…”
Section: Introductionmentioning
confidence: 99%
“…Here, a concordant rather than compliant understanding of adherence may also act to augment adherence rates . Adherence tends to be highest in childhood (≤12 years) and lowering in adolescents and young adults corresponding to the transition from parental care to self‐care . In a global survey, adherence dropped from 90% to 54% when 13‐18‐year‐olds started self‐infusing .…”
Section: Resultsmentioning
confidence: 99%
“…Among haemophilic patients in the Western world, adolescents (13‐17‐year‐olds) and young adults (18 to 25‐30‐year‐olds depending on the study) reportedly have the lowest adherence levels compared to other age groups . These patients go through major physical and psychosocial changes challenging the transition to self‐care …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation